Both GSK-3β/CRMP2 and CDK5/CRMP2 Pathways Participate in the Protection of Dexmedetomidine Against Propofol-Induced Learning and Memory Impairment in Neonatal Rats. (11th June 2019) - Li, Junhua; Guo, Mingyan; Liu, Yafang; Wu, Guiyun; Miao, Liping; Zhang, Jing; Zuo, Zhiyi; Li, Yujuan
Abstract: Dexmedetomidine has been reported to ameliorate propofol-induced neurotoxicity in neonatal animals. However, the underlying mechanism is still undetermined. Glycogen synthase kinase-3β (GSK-3β), cycline-dependent kinase-5 (CDK5), and Rho-kinase (RhoA) pathways play critical roles in neuronal development. The present study is to investigate whether GSK-3β, CDK5, and RhoA pathways are involved in the neuroprotection of dexmedetomidine. Seven-day-old (P7) Sprague Dawley rats were anesthetized with propofol for 6 h. Dexmedetomidine at various concentrations were administered before propofol exposure. Neuroapoptosis, the neuronal proliferation, and the level of neurotransmitter in the hippocampus were evaluated. The effects of GSK-3β inhibitor SB415286, CDK5 inhibitor roscovitine, or RhoA inhibitor Y276321 on propofol-induced neurotoxicity were assessed. Propofol-induced apoptosis in the hippocampal neurons and astrocytes, inhibited neuronal proliferation in the dentate gyrus region, down-regulated the level of γ-aminobutyric acid and glutamate in the hippocampus, and impaired long-term cognitive function. These harmful effects were reduced by pretreatment with 50 μg·kg −1 dexmedetomidine. Moreover, propofol-activated GSK-3β and CDK5 pathways, but not RhoA pathway, by reducing the phosphorylation of GSK-3β (ser 9), increasing the expression of CDK5 activator P25 and increasing the phosphorylation of their target sites on collapsin response mediator protein 2 (CRMP2) shortly after exposure. These effects were reversed by pretreatment with 50 μg·kg −1 dexmedetomidine. Furthermore, SB415286 and roscovitine, not Y276321, attenuated the propofol-induced neuroapoptosis, brain cell proliferation inhibition, γ-aminobutyric acid and glutamate downregulation, and learning and memory dysfunction. Our results indicate that dexmedetomidine reduces propofol-induced neurotoxicity and neurocognitive impairment via inhibiting activation of GSK-3β/CRMP2 and CDK5/CRMP2 pathways in the hippocampus of neonatal rats.